Lithium titanate coated graphite composite material, preparation method thereof, and secondary battery, battery module, battery pack, and electrical device containing the same

By coating lithium titanate on the graphite material of the lithium-ion battery and preparing composite materials by heating reaction and spray drying, the problem of rising anode potential of lithium-ion batteries under low charging state is solved, and the battery performance and safety is improved.

CN115842122BActive Publication Date: 2025-03-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210269069.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-18
Publication Date
2025-03-18
Estimated Expiration
2042-03-18

AI Technical Summary

Technical Problem

In the low charging state of lithium-ion batteries, the reaction of active lithium in graphite carbon anode materials with the electrolyte causes the anode potential to rise, resulting in problems such as SEI membrane decomposition, sudden gas production and degradation of battery performance.

Method used

Lithium titanate coated graphite composite material is prepared by coating lithium titanate on the graphite material, and heating reaction and spray drying are used to prepare a dense and uniform coating layer to inhibit the rise of the anode potential.

Benefits of technology

It effectively reduces the consumption of active lithium in graphite, inhibits the rise of the anode potential, avoids the decomposition of SEI membrane, and improves the storage performance and safety of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115842122B_ABST
    Figure CN115842122B_ABST
Patent Text Reader

Abstract

The present invention provides a lithium titanate-coated graphite composite material, a preparation method thereof, and a secondary battery, a battery module, a battery pack, and an electrical device containing the same. The preparation method comprises heating a titanium source compound, a lithium source compound, graphite, a chelating agent, and a solvent at 40-220°C to obtain a slurry C; then drying and calcining the slurry C to obtain a lithium titanate-coated graphite composite material. The preparation method is conducive to forming a dense and uniform lithium titanate coating layer, and has the advantages of being green and environmentally friendly; and the lithium titanate-coated graphite composite material is applied in a secondary battery, and the storage performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium battery technology, and in particular to a lithium titanate-coated graphite composite material, a preparation method thereof, and a secondary battery, a battery module, a battery pack, and an electrical device containing the same. Background Art

[0002] In recent years, as the application scope of lithium-ion batteries has become more and more extensive, lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. However, when lithium-ion batteries are in a low charge state SOC for a long time, the active lithium in the graphite carbon negative electrode material reacts with the electrolyte, causing the anode potential to rise. When the anode potential rises to the decomposition potential of the SEI film (1.8V), it will cause the SEI film to decompose, resulting in a sudden increase in gas production, which has serious safety hazards and reduces the performance of the battery.

[0003] To solve these problems, the main method is to make graphite materials contain lithium titanate by doping and coating. Among them, the use of lithium titanate coated graphite composite material is a relatively effective means. However, the method for preparing the composite material has the disadvantages of being difficult to industrialize, immature process technology, and environmentally unfriendly, and the density of the lithium titanate coating layer formed is low.

[0004] Therefore, the existing preparation method of graphite composite materials containing lithium titanate still needs to be improved. Summary of the invention

[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a method for preparing a lithium titanate-coated graphite composite material, which has a dense and uniform lithium titanate coating layer, which is beneficial for suppressing the increase of anode potential and improving the storage performance of the battery when making a secondary battery.

[0006] In order to achieve the above objectives, the present application provides a method for preparing a lithium titanate-coated graphite composite material.

[0007] The first aspect of the present application provides a method for preparing a lithium titanate-coated graphite composite material, the method comprising heating a titanium source compound, a lithium source compound, graphite, a chelating agent and a solvent at 40-220°C to react to obtain a slurry C; then drying and calcining the slurry C to obtain a lithium titanate-coated graphite composite material.

[0008] In an optional embodiment, the method for preparing a lithium titanate-coated graphite composite material comprises the following steps:

[0009] S1: mixing a titanium source compound, a lithium source compound, graphite, a chelating agent and a solvent to obtain a suspension B;

[0010] S2: heating the suspension B at 40-220°C to obtain slurry C;

[0011] S3: Drying and calcining the slurry C to obtain a lithium titanate-coated graphite composite material.

[0012] The lithium titanate-coated graphite composite material prepared in this way, when used as an anode material for a secondary battery, is beneficial to reducing the consumption of active lithium in the graphite, inhibiting the increase in anode potential, and avoiding the problem of sudden increase in gas production.

[0013] In an optional embodiment, in step S1, the titanium source compound is selected from at least one of isopropyl titanate, tetrabutyl titanate, and titanium dioxide; the lithium source compound is selected from at least one of lithium acetate, lithium hydroxide, lithium nitrate, and lithium carbonate.

[0014] The lithium titanate prepared from the titanium source compound and the lithium source compound has a lithium deintercalation potential of about 1.55 V. Moreover, when the graphite coated with lithium titanate is used as an anode, the anode potential rises more slowly, thereby suppressing the anode potential from rising to the decomposition potential of the SEI film of 1.8 V, thereby improving the storage performance of the secondary battery.

[0015] In an optional embodiment, in step S1, the chelating agent is selected from at least one of ammonium carbonate, ammonium bicarbonate, oxalic acid, urea, citric acid, ammonium formate, and ammonium oxalate. The chelating agent can react with the lithium source compound and the titanium source compound to form a corresponding chelate.

[0016] In an optional embodiment, in step S2, the suspension B is heated at 50-90°C for a reaction time of 2-14 hours, and optionally 8-12 hours, which is conducive to forming a dense and uniform coating layer.

[0017] In an optional embodiment, in step S3, drying is performed by spray drying, the feed inlet temperature is 120-250°C, optionally 150-200°C, and the feed pump speed is 3-40L / min, optionally 3-10L / min. By spray drying, solid-liquid separation can be performed directly, thereby avoiding the filtration operation and the loss of a large amount of eluent (such as water or organic solvent) associated therewith. This is conducive to improving production efficiency, saving production costs, and reducing environmental pollution.

[0018] The second aspect of the present application provides a lithium titanate-coated graphite composite material, which is obtained by the method for preparing the lithium titanate-coated graphite composite material provided by the first aspect of the present application.

[0019] In an optional embodiment, the content of lithium titanate in the lithium titanate-coated graphite composite material is 0.1-10% by weight, optionally 1-3% by weight, based on the weight of graphite.

[0020] The weight of graphite is the weight of graphite added during the preparation process. Due to the presence of lithium titanate, the composite material has a higher platform voltage (about 1.55V), so it can effectively inhibit the increase of the anode potential of the lithium ion battery, thereby avoiding the decomposition of the SEI film (the decomposition voltage is 1.8V) and reducing the gas production.

[0021] In an optional embodiment, the specific surface area SSA of the lithium titanate-coated graphite composite material is 1.1-2.1 m 2 / g, optional 1.22-1.99m 2 This is beneficial to reduce the exposure of active lithium in graphite to the electrolyte and improve the cycle performance and storage performance of the secondary battery.

[0022] The third aspect of the present application provides a secondary battery, which comprises the lithium titanate-coated graphite composite material prepared by the preparation method described in the first aspect of the present application, or the lithium titanate-coated graphite composite material described in the second aspect of the present application.

[0023] A fourth aspect of the present application provides a battery module, which includes the secondary battery described in the third aspect of the present application.

[0024] The fifth aspect of the present application provides a battery pack, which includes the battery module described in the fourth aspect of the present application.

[0025] The sixth aspect of the present application provides an electrical device, which includes at least one of the secondary battery described in the third aspect of the present application, the battery module described in the fourth aspect of the present application, or the battery pack described in the fifth aspect of the present application.

[0026] The secondary battery of lithium titanate coated graphite composite material provided in the present application has improved storage performance, and produces less gas when placed for a long time at low SOC. Accordingly, the battery pack, battery module and power-consuming device provided in the present application have good storage capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is an electron microscope image of the lithium titanate-coated graphite composite material of Example 1;

[0028] Figure 2 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0029] Figure 3 yes Figure 2 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0030] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application.

[0031] Figure 5It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0032] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0033] Figure 7 Schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.

[0034] Description of reference numerals:

[0035] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0036] Below, the negative electrode sheet and its manufacturing method, positive electrode sheet, secondary battery, battery module, battery pack and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0037] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3,4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-6. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0038] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0039] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0040] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0041] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, "include" and "comprising" may represent that other components not listed may also be included or only listed components may be included or only listed components may be included.

[0042] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0043] At present, the negative electrode material of lithium-ion batteries mainly adopts graphite-based carbon negative electrode materials. The surface of this material will form a solid electrolyte membrane (SEI membrane) during the formation process of the battery to hinder the reaction between active lithium and electrolyte and reduce gas production. However, since the graphite is in a non-platform area during the storage process of lithium-ion batteries at low charge state SOC (including 0% SOC), the active lithium in the graphite and the electrolyte continue to undergo reduction reactions, resulting in a decrease in active lithium and a rapid increase in anode potential. When the anode potential rises to 1.8V, the SEI membrane decomposes and produces a large amount of gas, causing the battery to bulge and deteriorate in battery performance.

[0044] To solve this problem, the main method is to make graphite materials contain lithium titanate (LTO) by doping, coating or coating. Among them, the use of LTO coated graphite composite materials is a relatively effective means. The preparation methods of the composite materials are mainly: 1. Sol-gel method, which requires the addition of inorganic film-forming additives and organic solvents, and the coating layer formed is not dense, and the process is complicated and pollutes the environment; 2. Atomic layer deposition method, the process is immature and difficult to use for large-scale production; 3. Co-precipitation method, including stirring a dispersion containing a lithium source compound, a titanium source compound, graphite and a chelating agent at room temperature, then filtering the slurry, washing the filter cake with a large amount of solvent, drying and crushing; the coating layer of the composite material formed in this way has a low density, is time-consuming and costly.

[0045] The inventors have discovered that, in the deposition method, the present invention can improve the density of the lithium titanate coating by heating the dispersion and spray drying the slurry, and directly perform solid-liquid separation using spray drying, thereby avoiding the waste of a large amount of solvent caused by filtering operations, thereby reducing time costs, economic costs, and environmental costs.

[0046] Therefore, the present application proposes to provide a lithium titanate-coated graphite material and a preparation method thereof, aiming to improve the density of the lithium titanate coating layer, save costs, and improve battery storage performance and other technical problems.

[0047] The first aspect of the present application provides a method for preparing a lithium titanate-coated graphite composite material, which comprises heating a titanium source compound, a lithium source compound, graphite, a chelating agent and a solvent at 40-220°C to react to obtain a slurry C; then drying and calcining the slurry C to obtain a lithium titanate-coated graphite composite material.

[0048] In some embodiments, the method for preparing a lithium titanate-coated graphite composite material comprises the following steps:

[0049] S1: mixing a titanium source compound, a lithium source compound, graphite, a chelating agent and a solvent to obtain a suspension B;

[0050] S2: heating the suspension B at 40-220°C to obtain slurry C;

[0051] S3: Drying and calcining the slurry C to obtain a lithium titanate-coated graphite composite material.

[0052] Through the above preparation method, a dense and uniform lithium titanate coating layer can be formed on the surface of the anode graphite. Figure 1The SEM image of Example 1 shown (Sigma-02-33 scanning electron microscope of ZEISS, Germany, with a magnification of 5K, a voltage of 10KV, and a scale of 1μm) is shown. This is beneficial to reducing the active area of ​​direct contact between graphite and electrolyte during storage of the secondary battery, inhibiting the consumption of active lithium in the anode, preventing the rise of the anode potential during storage, keeping the anode potential below the decomposition potential of the SEI film (1.8V), and avoiding the problem of sudden increase in gas production.

[0053] Wherein, step S1 includes the following specific steps:

[0054] S100: adding a titanium source compound and a lithium source compound into a solvent to obtain a mixed solution A;

[0055] S101: Add graphite and a chelating agent to the mixed solution A prepared in S101 to obtain a suspension B.

[0056] In the present invention, the "mixed liquid" used includes liquids in which all components contained can be completely dissolved in the solvent, and also includes liquids in which some components cannot be completely or partially dissolved in the solvent, such as suspensions, emulsions, dispersions, suspensions, etc.

[0057] The weight ratio of lithium source compound: titanium source compound: chelating agent: graphite is 1: (1.35-31.8): (4-22): (16-575), and can be optionally 1: (5-20): (5-30): (40-250).

[0058] In some embodiments, in step S100, the titanium source compound is selected from at least one of isopropyl titanate, tetrabutyl titanate, and titanium dioxide; the lithium source compound is selected from at least one of lithium acetate, lithium hydroxide, lithium nitrate, and lithium carbonate; the added amounts of the titanium source compound and the lithium source compound are such that the molar ratio of titanium element to lithium element is (1.25-2.25):1, optionally (1.5-2.0):1.

[0059] The lithium titanate obtained by using titanium source compounds and lithium source compounds as raw materials has a lithium deintercalation potential of about 1.55V; further, when the graphite coated with lithium titanate is used as an anode, the anode potential rises relatively slowly, thereby suppressing the anode potential from rising to the decomposition potential of the SEI film of 1.8V, avoiding a sudden increase in gas production, and improving the storage performance of the secondary battery.

[0060] Optionally, in step S100, a surfactant is further added, which is selected from at least one of cetyl trimethyl ammonium bromide, hydroxyethyl cellulose, poloxamer, sodium cetyl benzene sulfonate, polyvinyl pyrrolidone, sodium dodecyl sulfate, polyvinyl alcohol, and sodium oleate, and the surfactant used is 1-5% by weight, and optionally 2-3% by weight, based on the weight of the titanium source compound. Thus, the titanium source compound and the lithium source compound are fully dispersed in the solvent, which is conducive to their complete dissolution in the solvent.

[0061] In step S100, the solvent may be deionized water, an organic solvent, or a mixed solution of deionized water and an organic solvent; the organic solvent is selected from at least one of methanol, ethanol, isopropanol, polyethylene glycol, ethylene glycol, glycerol, propylene glycol, benzyl alcohol, phenylethyl alcohol, dimethylformamide, acetonitrile, dimethyl sulfoxide, oleic acid and oleylamine. Optionally, the present invention uses only deionized water as a solvent, and does not include any other organic solvent. Therefore, the method of the present invention is environmentally friendly and can avoid environmental pollution caused by organic solvents, and the corresponding post-processing steps or processes.

[0062] In step S101, graphite is selected from natural graphite or artificial graphite.

[0063] In some embodiments, in the specific step S101 included in step S1, the chelating agent is selected from at least one of ammonium carbonate, ammonium bicarbonate, oxalic acid, urea, citric acid, ammonium formate, and ammonium oxalate; the chelating agent is used to react with the lithium source compound and the titanium source compound to generate corresponding chelates.

[0064] In step S101, the stirring time is 0.5 to 2.5 hours, and optionally 1 to 2 hours.

[0065] In some embodiments, in step S2, the suspension B is reacted at 50-90° C. for 2-14 hours, or 8-12 hours. This is beneficial for regulating the morphology of the lithium titanate coating layer, better exerting the coating effect of lithium titanate on graphite, and forming a dense and uniform coating layer.

[0066] In some embodiments, in step S3, drying is performed by spray drying, the feed inlet temperature is 120-250°C, optionally 150-200°C, and the feed pump speed is 3-40 L / min, optionally 3-10 L / min.

[0067] The slurry C is dried and granulated by spray drying to obtain a precursor powder of a lithium titanate-coated graphite composite material, which can not only directly separate the solid and liquid, thereby reducing the waste of water resources (compared to the prior art, which usually uses a filtering operation and causes a large amount of water loss), but also improves the density of the coating layer. Therefore, the method of the present invention is a green preparation process.

[0068] In step S3, the precursor powder of the lithium titanate-coated graphite composite material obtained after drying is calcined in an inert atmosphere. The inert atmosphere can be argon Ar, nitrogen N2 or other mixed gases. The calcination temperature is 600-900°C and the calcination time is 4-12h to obtain the lithium titanate-coated graphite composite material of the present invention.

[0069] The second aspect of the present application provides a lithium titanate-coated graphite composite material, which is obtained by the above-mentioned preparation method. Due to the presence of a dense and uniform lithium titanate coating layer and a high platform voltage (about 1.55V) of lithium titanate, the composite material can effectively reduce the consumption of active lithium in graphite, inhibit the rise of the anode potential of the lithium ion battery, thereby avoiding the decomposition of the SEI film (1.8V) and reducing the gas production.

[0070] In some embodiments, the content of lithium titanate in the lithium titanate-coated graphite composite material is 0.1-10% by weight, optionally 1-3% by weight, based on the weight of graphite, and the content of lithium titanate is calculated by the ratio of the weight of lithium titanate to the weight of added graphite. When the content of lithium titanate is too low, less than the lower limit of 0.1% by weight, the graphite coating is not dense enough and the rise of the anode potential cannot be effectively suppressed; when the content of lithium titanate is too high, greater than the upper limit of 10% by weight, it is not conducive to the delithiation of the anode active material.

[0071] In the present invention, lithium titanate (chemical formula is Li4Ti5O 12 The weight of lithium titanate (molecular weight 460) is calculated based on the molar amount of lithium contained in the lithium source compound. For example, when the lithium source compound used is 1 mol of lithium acetate, the molar amount of lithium titanate obtained is 0.25 mol, and the weight is 0.25×460=115 g.

[0072] In some embodiments, the specific surface area SSA of the lithium titanate-coated graphite composite material is 1.1-2.1 m 2 / g, optional 1.22-1.99m 2 / g. This is beneficial for the composite material to have good surface stability when used as an anode active material, and can effectively reduce the exposure of active lithium in graphite to the electrolyte, thereby improving the cycle performance and storage performance of the secondary battery. It should be understood that the lithium titanate-coated graphite composite material of the present application can be used not only for lithium batteries, but also for any other battery, battery module, battery pack or electrical device that needs to reduce gas production and improve storage.

[0073] The particle size of the lithium titanate-coated graphite composite material of the present invention is 5-45 μm, and the volume median particle size Dv50 is 13-20 μm.

[0074] The secondary battery, battery module, battery pack and electric device of the present application are described below.

[0075] Secondary battery

[0076] In one embodiment of the present application, a secondary battery is provided, comprising the lithium titanate-coated graphite composite material of the present application.

[0077] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0078] [Positive electrode]

[0079] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.

[0080] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0081] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0082] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0083] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0084] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0085] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0086] [Negative electrode]

[0087] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, and the negative electrode film layer includes a negative electrode active material.

[0088] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0089] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0090] In some embodiments, the negative electrode active material is a lithium titanate-coated graphite composite material obtained by the preparation method of the present invention.

[0091] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0092] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0093] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0094] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0095] [Electrolytes]

[0096] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte).

[0097] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0098] In some embodiments, the electrolyte salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0099] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0100] In some embodiments, the electrolyte may also optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature performance, etc.

[0101] [Isolation film]

[0102] In some embodiments, the secondary battery further includes a separator. The separator is disposed between the positive electrode plate and the negative electrode plate to serve as a separator. The present application has no particular restrictions on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.

[0103] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0104] [Outer packaging]

[0105] In some embodiments, the secondary battery may include an outer package for packaging the positive electrode sheet, the negative electrode sheet and the electrolyte. As an example, the positive electrode sheet, the negative electrode sheet and the separator may be stacked or wound to form a stacked structure battery cell or a wound structure battery cell, and the battery cell is packaged in the outer package; the electrolyte may be an electrolyte, and the electrolyte is infiltrated in the battery cell. The number of batteries in the secondary battery may be one or more, which can be adjusted according to demand.

[0106] In one embodiment, the present application provides an electrode assembly. In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly by a winding process or a lamination process. The outer packaging can be used to package the above electrode assembly and the electrolyte.

[0107] In some embodiments, the outer packaging of the secondary battery may be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc. In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc.

[0108] Method for preparing secondary battery

[0109] In one embodiment, the present application provides a method for preparing a secondary battery, wherein the negative electrode sheet described in the present application or the negative electrode sheet prepared according to the method described in the present application is used.

[0110] The preparation of the secondary battery may also include the step of assembling the negative electrode sheet, the positive electrode sheet and the electrolyte of the present application to form a secondary battery. In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be wound or stacked in sequence, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, thereby obtaining a battery cell. The battery cell is placed in an outer package, and the electrolyte is injected and sealed to obtain a secondary battery. The battery group margin of the secondary battery is 90-95%.

[0111] In some embodiments, the preparation of the secondary battery may further include the step of preparing a positive electrode sheet. As an example, the positive electrode active material, the conductive agent and the binder may be dispersed in a solvent (e.g., N-methylpyrrolidone, referred to as NMP) to form a uniform positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, a positive electrode sheet is obtained.

[0112] In some embodiments, the preparation of a secondary battery includes the step of preparing a negative electrode sheet according to the method described in the present application.

[0113] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 2 The secondary battery 5 is a square structure as an example.

[0114] In some embodiments, reference Figure 3 , the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0115] Power-consuming device, battery module or battery pack

[0116] In one embodiment, the present application provides an electrical device, a battery module or a battery pack, wherein the electrical device, the battery module or the battery comprises a secondary battery as described in the present application or a secondary battery prepared according to the method described in the present application.

[0117] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0118] Figure 44 is an example of a battery module. Figure 4 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0119] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0120] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0121] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0122] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0123] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0124] Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0125] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0126] Example

[0127] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0128] 1. Preparation Example

[0129] Example 1

[0130] (1) 1.42 g of isopropyl titanate (0.005 mol) and 0.198 g of lithium acetate (0.003 mol) were dissolved in 100 ml of deionized water, with the molar ratio of Ti element (based on isopropyl titanate) to Li element (based on lithium acetate) being 5:3, and then 0.0345 g of surfactant hexadecyltrimethylammonium bromide was added to prepare a mixed solution A;

[0131] (2) 1.19 g of ammonium bicarbonate (0.015 mol) was added to the mixed solution A, and 34.5 g of artificial graphite was added, and the mixture was stirred for 1 h to form a suspension B;

[0132] (3) The mixed solution B was then transferred to a stainless steel reactor with a polytetrafluoroethylene lining in a water heating box, and heated at 60° C. for 12 h to obtain slurry C;

[0133] (4) Slurry C was spray-dried to obtain precursor powder of lithium titanate-coated graphite. The feed inlet temperature of the spray drying was 180° C. and the feed inlet pump speed was 5 L / min.

[0134] (5) The powder obtained in step (4) was calcined in a nitrogen inert atmosphere at 600° C. for 8 h to obtain a lithium titanate-coated graphite composite material.

[0135] The prepared lithium titanate coated graphite composite material has a lithium titanate content of 1 wt %, expressed as GR@1wt%LTO. The SEM image thereof is shown in the attached Figure 1 (Magnification: 5K, voltage: 10KV, scale: 1μm, Sigma-02-33 scanning electron microscope from ZEISS, Germany).

[0136] The specific surface area (SSA) of lithium titanate-coated graphite composite material is 1.99 m 2 / g, Dv10 is 10.5μm, Dv50 is 17.6μm, Dv90 is 29.1μm, and Dv99 is 38.5μm.

[0137] Example 2

[0138] The steps of Example 1 were repeated, except that steps 1 and 2 were:

[0139] (1) 2.84 g of isopropyl titanate (0.01 mol) and 0.396 g of lithium acetate (0.006 mol) were dissolved in 100 ml of deionized water, with the molar ratio of Ti element (based on isopropyl titanate) to Li element (based on lithium acetate) being 5:3, and then 0.069 g of surfactant hexadecyltrimethylammonium bromide was added to prepare a mixed solution A;

[0140] (2) Add 2.38 g of ammonium bicarbonate to the mixed solution A, and add 34.5 g of artificial graphite, and stir for 1 h to react to form a suspension B;

[0141] In the prepared lithium titanate-coated graphite composite material, the content of lithium titanate is 2 weight %, expressed as GR@2wt%LTO.

[0142] The specific surface area (SSA) of lithium titanate-coated graphite composite material is 1.20 m 2 / g, Dv10 is 7.3μm, Dv50 is 15.6μm, Dv90 is 29.6μm, and Dv99 is 40.9μm.

[0143] Example 3

[0144] The steps of Example 1 were repeated, except that steps 1 and 2 were:

[0145] (1) 4.26 g of isopropyl titanate (0.015 mol) and 0.594 g of lithium acetate (0.009 mol) were dissolved in 100 ml of deionized water, with the molar ratio of Ti element (based on isopropyl titanate) to Li element (based on lithium acetate) being 5:3, and then 0.11 g of surfactant hexadecyltrimethylammonium bromide was added to prepare a mixed solution A;

[0146] (2) Add 3.57 g of ammonium bicarbonate to the mixed solution A, and add 34.5 g of artificial graphite, and stir for 1 h to form a suspension B;

[0147] In the prepared lithium titanate-coated graphite composite material, the content of lithium titanate is 3 weight %, expressed as GR@3wt%LTO.

[0148] The specific surface area (SSA) of lithium titanate-coated graphite composite material is 1.22 m 2 / g, Dv10 is 8.5μm, Dv50 is 16.2μm, Dv90 is 28.9μm, and Dv99 is 40.3μm.

[0149] Embodiment 4-8

[0150] The steps of Example 1 were repeated, except that the temperatures of the heating reaction in step (3) were 40, 50, 90, 200, and 220° C., respectively.

[0151] Example 9

[0152] The steps of Example 1 were repeated, except that the heating reaction time in step (3) was 8 h.

[0153] Examples 10-13

[0154] The steps of Example 1 were repeated, except that the feed inlet temperatures of the spray drying in step (4) were 100, 150, 200, and 250° C., respectively.

[0155] The parameters are summarized in Table 1.

[0156] 2. Preparation Comparative Example

[0157] Comparative Example 1

[0158] The steps of Example 1 were repeated, except that the heating reaction in step 3 was not performed.

[0159] Comparative Example 2

[0160] The steps of Example 1 were repeated, except that the heating reaction in step 3 was not performed, and in step 4, the slurry C was filtered and then dried in a vacuum oven at 60° C. for 12 h.

[0161] 3. Application Examples

[0162] 1. Preparation of Secondary Batteries

[0163] (1) Preparation of negative electrode sheet: The lithium titanate-coated graphite composite material prepared in Examples 1 and 4-13 and Comparative Examples 1-2 is mixed with styrene-butadiene rubber (SBR), conductive agent Super P carbon black, and sodium methyl cellulose (CMC) in a weight ratio of 96.5%:1.8%:0.5%:1.2% to prepare a slurry, and the prepared slurry is coated on a copper foil current collector, dried in an oven, and then cold pressed for use. The compression range is: 1.5 g / cm 3 ;

[0164] (2) Positive electrode: lithium metal sheet is used as the counter electrode;

[0165] (3) preparing an electrolyte: mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a volume ratio of 1:1:1, and then uniformly dissolving LiPF6 in the above solution to obtain an electrolyte, wherein the concentration of LiPF6 is 1 mol / L;

[0166] Diaphragm: Polyethylene (PE) film is used as the isolation membrane with a thickness of 12μm.

[0167] (4) Preparation of secondary battery: The above parts were manually wound into a secondary battery in an argon-protected glove box. The outer packaging was a plastic shell of 48 mm (width) × 204 mm (length) × 86 mm (height). The thickness of the shell was 1.5 mm. The battery group margin was 93%.

[0168] 2. Preparation of three-electrode cells

[0169] The preparation operation is similar to that of the secondary battery, except that in step (4), during manual winding, a copper wire is implanted on the anode side and in contact with the anode, and a lithium plating operation is performed before measurement.

[0170] 4. Determination Method

[0171] 1. Determination of specific surface area

[0172] The specific surface area analysis was performed using a gas adsorption method according to GB / T19587-2004 <Determination of the specific surface area of ​​solid substances by gas adsorption specific surface area method> for the lithium titanate-coated graphite composite materials prepared in Examples 1-3.

[0173] 2.D V 50. D V 10. D V 90 and Dv99 testing methods

[0174] With reference to the standard GB / T19077.1-2016, a laser particle size analyzer (Malven Master Size 3000) was used to measure the lithium titanate-coated graphite composite materials prepared in Examples 1-3.

[0175] 3. Full battery voltage test method:

[0176] The prepared secondary battery was discharged to 2.5 V at 25°C and then placed in a high and low temperature box at 70°C to monitor the change in the full battery voltage using a Xinwei tester.

[0177] 4. Anode potential test method:

[0178] The prepared three-electrode battery cell was discharged to 2.5 V at 25°C and then placed in a high and low temperature box at 70°C to monitor the change of anode potential using a Xinwei testing machine.

[0179] The results of the measured full cell voltage and anode potential on day 25 are summarized in Table 1.

[0180] Table 1: Relevant process parameters and performance data of Examples 1 and 4-13 and Comparative Examples 1-2

[0181]

[0182] According to the above results, the voltage of the battery in the embodiment of the present invention remains at a relatively high voltage level after being stored for 25 days in a low SOC state; the anode potential of the battery cell is relatively low, far less than the decomposition potential of the SEI film (1.8V). In contrast, in Comparative Examples 1-2, the full battery voltage and anode potential are not effectively improved.

[0183] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing a lithium titanate-coated graphite composite material, characterized in that: The method comprises the following steps: S1: mixing a titanium source compound, a lithium source compound, graphite, a chelating agent and a solvent to obtain a suspension B, wherein the titanium source compound is selected from at least one of isopropyl titanate, tetrabutyl titanate and titanium dioxide, the lithium source compound is selected from at least one of lithium acetate, lithium hydroxide, lithium nitrate and lithium carbonate, and the chelating agent is selected from at least one of ammonium carbonate, ammonium bicarbonate, oxalic acid, urea, citric acid, ammonium formate and ammonium oxalate; S2: The suspension B is heated at 40-220° C. to obtain slurry C; S3: The slurry C is spray-dried and calcined to obtain the lithium titanate-coated graphite composite material.

2. The method according to claim 1, wherein in step S2, the suspension B is heated at 50-90°C for a reaction time of 2-14 hours.

3. The method according to claim 1, wherein in step S2, the suspension B is heated at 50-90°C for a reaction time of 8-12 hours.

4. The method according to claim 1, wherein in step S3, during the spray drying process, the feed inlet temperature is 120-250°C.

5. The method according to claim 1, wherein in step S3, during the spray drying process, the feed inlet temperature is 150-200°C.

6. A lithium titanate-coated graphite composite material, prepared by the method according to any one of claims 1 to 5.

7. The lithium titanate-coated graphite composite material according to claim 6, characterized in that: The content of lithium titanate in the lithium titanate-coated graphite composite material is 0.1-10% by weight, based on the weight of graphite.

8. The lithium titanate-coated graphite composite material according to claim 6, characterized in that: The content of lithium titanate in the lithium titanate-coated graphite composite material is 1-3% by weight, based on the weight of graphite.

9. The lithium titanate-coated graphite composite material according to any one of claims 6 to 8, characterized in that: The specific surface area SSA of the lithium titanate-coated graphite composite material is 1.1-2.1 m 2 / g.

10. The lithium titanate-coated graphite composite material according to any one of claims 6 to 8, characterized in that: The specific surface area SSA of the lithium titanate-coated graphite composite material is 1.22-1.99 m 2 / g.

11. A secondary battery, characterized in that: The invention comprises the lithium titanate-coated graphite composite material according to any one of claims 6 to 10.

12. A battery module, characterized in that: The secondary battery according to claim 11 is included.

13. A battery pack, characterized in that: Comprising the battery module as claimed in claim 12.

14. An electrical device, characterized in that: The battery comprises at least one selected from the secondary battery of claim 11 , the battery module of claim 12 , or the battery pack of claim 13 .

Citation Information

Patent Citations

  • Graphite composite material, preparation method and application thereof

    CN106374093A

  • Nano lithium titanate coated modified graphite negative electrode material as well as preparation method and application thereof

    CN113363444A